PENGARUH PEMBERITAAN KASUS PENIPUAN UMROH TERHADAP MINAT MASYARAKAT DALAM MEMILIH BIRO PERJALANAN UMROH - Selpi, Selpi; Setiawan, Romi Adetio; Makmur, Makmur (ITB AAS Indonesia Surakarta, 2024)
The Umrah pilgrimage is an appropriate choice for Muslims to visit the Baitullah, in Mecca, but the prevalence of Umrah fraud cases has caused trauma among pilgrims in selecting Umrah travel agencies. This research aims to assess whether there is an influence of reporting on Umrah fraud cases on public interest in choosing Umrah travel agencies in Linggae Lintang, South Sumatra. To test this hypothesis, the researchers employed a quantitative descriptive method with a sample of 70 respondents. The data analysis technique used was simple linear regression with the assistance of SPSS software. The results of the study indicated that there is a significant influence of reporting on Umrah fraud cases on public interest in choosing Umrah travel agencies.